Anti-inflammatory and antiproliferative prenylated chalcones from Hedysarum gmelinii. Issue 11 (2nd November 2018) - Liu, Yi; Zhang, Jun; Wen, Ran; Tu, Guang-Zhong; Chen, Hu-Biao; Liang, Hong; Zhao, Yu-Ying
Abstract: Five new prenylated chalcones hedysarumines C-G (1 –5 ), along with eight known chalcones (6 –13 ) all of which were isolated from the genus Hedysarum for the first time, were isolated from the roots of Hedysarum gmelinii by chromatographic methods. Their structures were determined by extensive spectroscopic techniques. The isolated chalcones (2 –13 ) and previously isolated prenylated chalcones (14 –16 ) were evaluated for antiproliferative activity against five human cancer cell lines (HepG2, A549, Du145, BGC823, and HCT116) and in vitro anti-inflammatory activity. Compounds5, 10, and15 inhibited NO production induced by lipopolysaccharide in BV-2 cells, with IC50 values ranging from 3.25 to 8.48 μM. Compounds4 and11 showed moderate antiproliferative activity to selective human cancer cell lines, with the IC50 values of4 and11 against A549 cell line being 7.79 and 9.67 μM, respectively, and the IC50 value of11 against HCT116 cell line being 8.85 μM. Abstract :